Performance Measurement of Office Boys Against Student Satisfaction at Universitas Potensi Utama using HR Scorecard - Dicky Abriansyah; Marwan Marwan (Industrial Engineering System and Management Journal, 2025)
This study aims to measure the performance of Office Boys using the Human Resource Scorecard (HRSC) method, which integrates people, strategy, and performance to create a competitive advantage. HRSC was chosen due to its ability to translate the organization's vision and strategy into measurable performance indicators both quantitatively and qualitatively. The analysis was conducted using the Analytical Hierarchy Process (AHP) approach to determine the weight of each perspective within the HRSC framework. The results show that the Internal Business Process perspective has the highest weight and Eigen Vector Normalization (EVN) value compared to other perspectives, indicating that internal processes are the most influential factor in evaluating Office Boy performance. Conversely, the Financial perspective had the lowest weight, implying a relatively smaller impact on overall performance improvement. These findings suggest that focusing on enhancing internal processes can significantly improve overall performance and serve as a foundation for developing more effective and sustainable human resource management strategies.